2011
DOI: 10.1097/bpb.0b013e32834493cb
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationship of the Risser sign, knee epiphysis, and bone age in determining skeletal maturity

Abstract: The purpose of our study was to correlate the chronological age with Risser staging, knee epiphyseal closure, and bone age by the Tanner and Whitehouse (TW3) or Greulich and Pyle (GP) method simultaneously, to find out the most correlated methods used to calculate the age in a Korean population. A case-control study was carried out in 293 children between the age of 9 and 18 years. Skeletal age was estimated by using the atlas of the GP and TW3 methods; knee epiphysis closure and the Risser staging were also n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The Risser staging system is often criticized for its inaccuracy [38], but it is still commonly used for guiding brace prescription and weaning. Many clinicians may use other skeletal maturity indices in addition to the Risser staging system to improve and facilitate more precise growth assessments, such as using the physeal closure at the knee, the phalanges, and the distal radius and ulna visible on the handwrist radiograph [8,12,16,32]. This can only be achieved by understanding how skeletal maturity indices behave and their effectiveness in evaluating growth.…”
Section: Discussionmentioning
confidence: 99%
“…The Risser staging system is often criticized for its inaccuracy [38], but it is still commonly used for guiding brace prescription and weaning. Many clinicians may use other skeletal maturity indices in addition to the Risser staging system to improve and facilitate more precise growth assessments, such as using the physeal closure at the knee, the phalanges, and the distal radius and ulna visible on the handwrist radiograph [8,12,16,32]. This can only be achieved by understanding how skeletal maturity indices behave and their effectiveness in evaluating growth.…”
Section: Discussionmentioning
confidence: 99%
“…As any one maturity index cannot cover the entire growth period comprehensively, multiple skeletal maturity measures are frequently employed for more accurate assessment. The Greulich and Pyle method, the Tanner and Whitehouse method, and the Risser sign are commonly used together for pediatric patients in daily practice worldwide [ 32 ]. Dimeglio previously found that Risser 0 can be subdivided into two periods with open or closed triradiate cartilage, and the Risser sign can be split according to the apophyseal closure of the greater trochanter.…”
Section: Discussionmentioning
confidence: 99%